The War, Postwar and Postmodern British Poets: Themes and Styles - Subanti, Gregorius (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2018)
British literature, especially poetry has experienced different phases and showed the unique faces from the early periods to what called modernity era. The multi-facetted poetry is inflected by the dynamic atmospheres faced by Britain as results of the responses of poetic artists to the ups and downs of British history, especially the industrial changes and the brutality of World War I and II. Poets responded the political, social and cultural waves with their own unique styles and moods. The traumatic Wars and their casualties were not the sole themes during the war or post war era poetry, some poets reacted the issues of their own ways. This paper will discuss the reaction of some British poets to the wars. The discussion sections will be parted into the general responses, and also the analysis of two post war poets namely Adrian Henry and James Berry to represent their era of 1960 and 1980. This study reveals some findings that the poets experienced WWI and WWII responded the wars in such dramatic and gloomy ways as they are closely affected by the effects of 1915-1945 wars. Adrian Henry lived in the era post-modern, 1960s, the effect should have recovered. His poetic style speaks itself. James Berry, a Black immigrant poet, voices his root, past experiences and hope for a new life. Despite the style and theme, they all flourish British poetry with their own uniqueness.Keywords: British poetry, postwar, postmodern, Adrian Henri, James Berry